Changes in Endothelial-Related Goagulation Proteins in Response to Venous Occlusion - Jennings, I; Luddington, R J; Harper, P L (Thrombosis and Haemostasis, 1991)
One hundred patients with a history of thrombophilia wer divided into two groups based on fibrinolytic response to venous occlusion. Good responders with a euglobulin clot lysis time ≤ 105 min showed significant release of tPA, PAI and vWE Of the poor responders with an ECIX > 105 min, 24% showed a subnormal increase in tPA, and a significant proportion of these also showed a reduced or absent rise in vWEWe have shown poor fibrinolytic response was related to either raised levels of PAI, poor release of both tPA and vWR or poor release of tPA or vWF alone suggesting different mechanisms of fibrinolytic impairment. Protein S levels were not significantly changed in either group following occlusion.